2001
DOI: 10.1093/jn/131.7.1890
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Spermidine and Spermine Participate in the Maturation of Galactosyltransferase Activity and Glycoprotein Galactosylation in Rat Small Intestine

Abstract: This study considered the role of dietary polyamines in the maturation of intestinal glycoprotein galactosylation during postnatal development. In the rat small intestine, O-glycan: beta-1,3-galactosyltransferase and N-glycan: beta-1,4-galactosyltransferase are, respectively, involved in the glycan chain biosynthesis of mucins and of glycoproteins in the brush border membranes. Their activities increase significantly at weaning, in parallel with a rise in the intestinal content of spermidine and spermine (as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 39 publications
0
11
1
1
Order By: Relevance
“…However, spermine significantly elevated gastric mucin content. This effect of spermine adds to its gastroprotective potential that might be attributed to enhancement of uridine diphosphate (UDP)-galactose: mucin galactosyltransferase activity, a key enzyme for the synthesis of mucin, as previously demonstrated in rat small intestine [40]. In addition, spermine stimulates gastrin release through activation of the calcium-sensing receptor on the G cell [41], which, in turn, stimulates mucin production [42].…”
Section: Discussionmentioning
confidence: 97%
“…However, spermine significantly elevated gastric mucin content. This effect of spermine adds to its gastroprotective potential that might be attributed to enhancement of uridine diphosphate (UDP)-galactose: mucin galactosyltransferase activity, a key enzyme for the synthesis of mucin, as previously demonstrated in rat small intestine [40]. In addition, spermine stimulates gastrin release through activation of the calcium-sensing receptor on the G cell [41], which, in turn, stimulates mucin production [42].…”
Section: Discussionmentioning
confidence: 97%
“…The results show that both medium and feed supplementation of galactose analogs, a polyamine and a non proteinogenic amino acid consistently and specifically reduced the level of galactosylation in fed-batch cultures. A report described the role of spermine in the maturation of intestinal galactosylation in rat intestine, showing that the amount of digested polyamines correlated with increased galactosyltransferase activity 239 . Interestingly, in the same study spermine had no influence on the galactosyltransferase activity in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In the small intestine, both enzyme activities are detected (Biol-N'garagba et al 2003;Greco et al 2001). In addition, a recent study has shown that activities of both β-1,4-GalT and β-1,3-GalT in the small intestine were reduced by feeding weanling rats dietary fat (Lenoir et al 2000).…”
Section: Discussionmentioning
confidence: 99%